Cartesian Ludo: A Mathematical Game to Explore the Concepts of Coordinates - Singla, Palvi; Hashmi, Nida (Educational Trend (A Journal of RIE, Ajmer - NCERT), 2025)
This study was designed to investigate the effect of mathematical game on students‘ understanding of Cartesian coordinates and plane. The study also aimed at assessing the role of mathematical games in making learning mathematics more interesting. Thus, both quantitative as well as qualitative research methodologies were applied. This study employed a nonequivalent control group quasi-experimental design. The control group comprised of students from class 5th to class 7th from three Delhi-based secondary schools. The control group was drawn through a stratified random sampling technique (based on two aspects - educational attainments and gender i.e. male and female students). The premise of the study was to find out whether, and to what extent, mathematical games can help in improving the understanding of mathematical concepts of students. Cartesian Ludo, a board-game based on Cartesian plane (with Origin, X-axis and Y-axis) and played with two dice and two to four tokens (resembling the traditional game of Ludo) was created and employed for this study. The pre-test and post-test analysis of the study revealed that the mathematical game approach is superior to the conventional method (such as monologic teaching pedagogy) in facilitating better learning outcomes for students.